Analisis Pengaruh Kemudahan Penggunaan dan Kebermanfaatan yang Dirasakan terhadap Keberlanjutan Penggunaan E-Wallet pada Pelaku UMKM di Indonesia Dimoderasi oleh Risiko Keamanan - Natasya Gabriella Tambunan; Vika Fitranita (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the effect of ease of use and perceived usefulness on the continued use of E-wallets in MSME players in Indonesia, with security risk as a moderating variable. The research method uses a quantitative approach with a survey involving 400 respondents of MSME players who use E-wallets in digital transactions, such as payments, revenue receipts, and payroll cycle management. The results of the analysis show that ease of use does not have a significant effect on the continued use of E-wallets. In contrast, perceived usefulness has a positive impact on the continued use of this technology. Security risks are proven to play a role in strengthening the relationship between ease of use and usefulness with the continued use of E-wallets. These findings indicate that even though users feel the benefits of using E-wallets, the perception of security risks remains an important factor that can reduce the intention to continue using these services.